A synergetic layered inorganic–organic hybrid film for conductive, flexible, and transparent electrodes - Devendra Singh (Nature Portfolio, 2019)
Layered electrodes with high conductivity and flexibility High conductivity and flexibility are preferred for flexible electrodes but they usually don’t blend well in one single material. Now the combination is achieved in a layered hybrid film. A team led by Prof Gilles Lubineau from King Abdullah University of Science and Technology, Saudi Arabia design layered transparent electrode with both high flexibility and high conductivity. A thin conductive layer of polymeric PEDOT:PSS is spun-coat on the flexible PET substrate, then the ITO layer is sputtered on top of the PEDOT:PSS layer at low temperature. Despite a simple process, the layered structure combines the advantages of ITO and PEDOT:PSS to show high conductivity under macroscopic strain up to 30%. This approach showcases a delicate way to avoid drawback of the brittleness of ITO and can be adopted in other stretchable and flexible devices.